PRELIMINARY STUDY OF SERVICE QUALITY AND PURCHASE INTENTIONS IN AN AIRPORT: A QUALITATIVE APPROACH - RUSHAMI ZIEN YUSOFF; ADI NUGROHO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2007)
This study was about the service quality perception and its relation to purchase intention in the airport industry. The main purpose of this study was to develop an understanding of the service quality perception in Airports by investigating the relationships of service quality in terms of creating purchase intentions. The study, however, included the perceptions of both international passengers and domestic concerning the current service levels. This study analyzes whether passengers may stay longer in the airport, recommend the airport to other people or pay higher tax if they are satisfied with the service offers by airport. This means that an assessment the ability of service quality to explain the variation in repeat purchase intention including interaction among variables. The results of this study show that despite service quality explain purchase intention relatively low, some findings relating that issues have been revealed.